Deinstitutionalization from the perspective of community-dwelling adults with a severe mental illness in Amsterdam: a cohort study protocol - Menno Segeren; Steve Lauriks; Martijn Kikkert; Jet Heering; Nick Lommerse; Gwen van Husen; Arnoud Verhoeff (BMC, 2022)
Abstract Background People with a severe mental illness (SMI) increasingly receive ambulatory forms of care and support. The trend of deinstitutionalization accelerated in the Netherlands from 2008 and onwards without sufficient understanding of its consequences. The study protocol herein focuses on deinstitutionalization from the perspective of adults with an SMI living within the community in Amsterdam and aims at delivering better insight into, amongst others, their recovery, quality of life, societal participation and needs for care and support. Methods A cohort design will be used. A representative sample of community-dwelling adults with an SMI, including those in care (n = 650) and not in care (n = 150), will be followed over time. During a two-year time period, participants will be interviewed twice using a wide-ranging set of validated instruments. Interview data will be matched with administrative data about the care process, as retrieved from their patient files. Primary outcomes are changes over time in recovery, societal participation and quality of life, controlled for the occurrence of adverse life-events during follow-up. Additionally, prevalence estimates of and associations between social functioning, safety and discrimination, substance use and health indicators will be investigated. Discussion The study protocol aims at delivering a comprehensive insight into the needs of community-dwelling adults with an SMI based on which ambulatory care and support can best be provided to optimally promote their social recovery and well-being.